If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 25 = y Reorder the terms: 25 + 4x = y Solving 25 + 4x = y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + 4x = -25 + y Combine like terms: 25 + -25 = 0 0 + 4x = -25 + y 4x = -25 + y Divide each side by '4'. x = -6.25 + 0.25y Simplifying x = -6.25 + 0.25y
| 2(8x-2)=12x+24 | | 4x+4-40=0 | | -2u^2+15u+25= | | .073x+0.34=9.1 | | .12x=y-105 | | y=(x*0.1)+(x*0.02)+5+100 | | 2x^5+3x^4-x^3+x^2-12= | | 7x^3-1-15x^3-4x^2+x-3= | | 3x+5=2x+6-4 | | -0.12q^2+1.8q-6=0 | | 33x+180=15 | | h(t)=-16t^2+800(t)+125 | | 4(v+5)=-2(9v-2)+8v | | 4x-(6x-2)=32 | | 6x^8+2x^4-5x^3+x^2-1= | | -2(-5v+8)-3v=3(v-7)-5 | | (3x^3+10x+5)-(x^3-4x-6)= | | 3w-5+3(3w+3)=-4(w+1) | | -5u-13=-2(u-7) | | 4x^3-8=100 | | 3.2+x=7.45 | | 9(y-4)=3y-6 | | x^3-3x=21 | | (3x^3+10x+5)-(x^3+4x-6)= | | -2x-23=3(x+4) | | 4c^3-8=100 | | -6(U+2)=4u+38 | | -3v+5(v-2)=-20 | | 14=5(x+5)+6x | | 14=4(w-4)-7w | | -c(5)-23=-18 | | x+16=2x+4 |